Empowering Shadow Teachers Through Inclusive English Module Development at Sekolah Alam Langit Biru Bengkulu - Muhammad Parli; Ria Angraini; Dian Susyla; Washlurachim Safitri; Hardiansyah Hardiansyah; Solehan Solehan; Nasir Muhammad (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: English instruction for inclusive students at Sekolah Alam Langit Biru Bengkulu is currently constrained by the absence of structured teaching modules and limited pedagogical training among shadow teachers, resulting in inconsistent instructional practices.Aims: This community service paper aims to describe the design, implementation, and evaluation of an inclusive English teaching module developed specifically for shadow teachers at Sekolah Alam Langit Biru Bengkulu, with a focus on practical capacity building and classroom applicability.Methods: The program involved seven shadow teachers and six inclusive students and was conducted through orientation, workshops, guided mentoring, module development using Canva, classroom try-out, and evaluation. Data were collected using teacher pretest–posttest questionnaires measuring instructional readiness and digital literacy, and student vocabulary assessments. All data were analyzed descriptively.Results: The findings indicate a notable improvement in shadow teachers’ instructional readiness and digital literacy, with average scores increasing by approximately 21% from pretest to posttest. In addition, student vocabulary scores improved in four out of six participants, with gains ranging from 17 to 30 points, particularly among those with lower initial proficiency.Conclusion: The program demonstrates that integrating accessible digital tools and multisensory media within a structured training framework is a feasible and effective approach to supporting inclusive English learning through shadow teachers.